1990
DOI: 10.1029/jd095id02p01817
|View full text |Cite
|
Sign up to set email alerts
|

Systematic variations in the concentration of NOx (NO Plus NO2) at Niwot Ridge, Colorado

Abstract: Measurements of the concentrations of NO and NO2 were made in the rural troposphere during a year's period in 1980–1981, during the summers of 1983, 1984, and 1987, and during the fall of 1984. The field site was located near Niwot Ridge, Colorado, at an elevation of 3 km. NO was measured with a chemiluminescence instrument, and NO2 was photolyzed to NO and measured by the same instrument. The performance of this instrument is discussed in detail. Aspects of the NOx (sum of NO and NO2) concentrations discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 63 publications
3
78
1
1
Order By: Relevance
“…Previous ambient studies at NWT have found typical wintertime (NO ? NO 2 ) values of 200-1,000 pptv (Parrish et al 1990), and it is not unusual that the sum of oxidized nitrogen gases (NO y ) can exceed 1 ppbv (Fahey et al 1986;Ridley et al 1990). Our experiments do not allow for an evaluation of the contribution of these other species to the detected NO 2 signal, nor do we have measurements that allow for an assessment of the NO 2 to NO conversion efficiency of our TEI 42TL instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Previous ambient studies at NWT have found typical wintertime (NO ? NO 2 ) values of 200-1,000 pptv (Parrish et al 1990), and it is not unusual that the sum of oxidized nitrogen gases (NO y ) can exceed 1 ppbv (Fahey et al 1986;Ridley et al 1990). Our experiments do not allow for an evaluation of the contribution of these other species to the detected NO 2 signal, nor do we have measurements that allow for an assessment of the NO 2 to NO conversion efficiency of our TEI 42TL instrument.…”
Section: Methodsmentioning
confidence: 99%
“…11d). These conditions can occur in winter on Niwot Ridge after a frontal system passes through the region (Parrish et al 1990). The temperature of the snow surface at NWT was estimated to be around 228C, which was very close to the dewpoint temperature (Fig.…”
Section: Surface Condensation Effects On Snow Temperature Changesmentioning
confidence: 99%
“…Several meteorological events occur just before the snowpack warm-up: 1) the wind speed dropped; 2) the abovecanopy wind direction continued downslope, but the subcanopy wind direction switched to upslope (i.e., decoupling occurred); 3) the water vapor content of the air reached a maximum; and 4) the dewpoint temperature (T d ) approached the snow surface temperature. Upslope winds at the site can be generated by diurnal surface heating, large-scale pressure gradients, or mesoscale phenomena due to the mountainous topography (Parrish et al 1990;Turnipseed et al 2004), with decoupling of the above-canopy and subcanopy air occurring within the forested areas ). In Fig.…”
Section: Surface Condensation Effects On Snow Temperature Changesmentioning
confidence: 99%
“…The forest is roughly 60 km northwest of a large urban region on the plains (the Denver, Colorado, metropolitan area). A series of experiments focused on photochemical processes in air established that pollutants from the Denver urban area can be transported to the Niwot Ridge forest by easterly winds in summer (Roberts et al, 1985;Parrish et al, 1990Parrish et al, , 1991. Although CH 4 was not measured in those studies, carbon monoxide at Niwot Ridge tends to be higher during summer easterly winds (Parrish et al, 1991).…”
Section: Environmental Conditions and Observed Ch 4 And Comentioning
confidence: 99%